2010
DOI: 10.1007/s00198-010-1412-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a multifaceted intervention to improve quality of osteoporosis care after wrist fracture

Abstract: For outpatients with wrist fractures, our multifaceted osteoporosis intervention was cost-effective. Healthcare systems implementing similar interventions should expect to save money, reduce fractures, and gain quality-adjusted life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…During the same period, hip fracture rates for the entire population of England had increased by almost 17%. These findings are broadly consistent with observational data reported by Dell and colleagues for the Kaiser Healthy Bones Program in the USA [23] and randomized control trial data reported by Majumdar and colleagues from Canada [24,25].…”
Section: Fracture Case Findingsupporting
confidence: 82%
“…During the same period, hip fracture rates for the entire population of England had increased by almost 17%. These findings are broadly consistent with observational data reported by Dell and colleagues for the Kaiser Healthy Bones Program in the USA [23] and randomized control trial data reported by Majumdar and colleagues from Canada [24,25].…”
Section: Fracture Case Findingsupporting
confidence: 82%
“…The use of a care coordinator to identify patients who have suffered a fragility fracture and to coordinate care within a multidisciplinary team has been demonstrated to significantly increase both the diagnosis and the treatment of osteoporosis following a fragility fracture [17,[22][23][24][25][26][27][28][29][30]. Furthermore, the use of a care coordinator has been demonstrated to be cost-effective [25,31,32]: Irrespective of the number of patients receiving case-managed care, the intervention reached a break-even threshold within 2 years. Limitations to this study include self-reporting of much of the data and a lack of information regarding vertebral fractures; non-vertebral fractures represent approximately 75% of all osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Both estimated the number of future hip fractures prevented and conducted sensitivity analyses that demonstrated a robust model with the coordinator programme dominant over usual care. Majumdar and colleagues [83] showed that the intervention cost $12 per patient and, for every 100 patients receiving the intervention, 3 fractures (1 hip fracture) would be prevented, 1.1 quality-adjusted life year gained, and $26,800 saved by the healthcare system over their remaining lifetime. A recent health economic analysis has established that the Glasgow FLS, in the UK, is cost-effective for the prevention of secondary fractures and is cost-saving.…”
Section: Cost-effectiveness Of Coordinator-based Systemsmentioning
confidence: 98%